Bio-inspired adhesive catechol-conjugated chitosan for biomedical applications: A mini review. (November 2015) - Ryu, Ji Hyun; Hong, Seonki; Lee, Haeshin
Graphical abstract: Abstract: The development of adhesive materials, such as cyanoacrylate derivatives, fibrin glues, and gelatin-based adhesives, has been an emerging topic in biomaterial science because of the many uses of these materials, including in wound healing patches, tissue sealants, and hemostatic materials. However, most bio-adhesives exhibit poor adhesion to tissue and related surfaces due to the presence of body fluid. For a decade, studies have aimed at addressing this issue by developing wet-resistant adhesives. Mussels demonstrate robust wet-resistant adhesion despite the ceaseless waves at seashores, and mussel adhesive proteins play a key role in this adhesion. Adhesive proteins located at the distal end (i.e., those that directly contact surfaces) are composed of nearly 60% of amino acids called 3, 4-dihydroxy-l -phenylalanine (DOPA), lysine, and histidine, which contain side chains of catechol, primary amines, and secondary amines, respectively. Inspired by the abundant catecholamine in mussel adhesive proteins, researchers have developed various types of polymeric mimics, such as polyethylenimine–catechol, chitosan–catechol, and other related catecholic polymers. Among them, chitosan–catechol is a promising adhesive polymer for biomedical applications. The conjugation of catechol onto chitosan dramatically increases its solubility from zero to nearly 60 mg/mL (i.e., 6% w/v) in pH 7 aqueous solutions. The enhanced solubility maximizes the ability of catecholamine to behave similar to mussel adhesive proteins. Chitosan–catechol is biocompatible and exhibits excellent hemostatic ability and tissue adhesion, and thus, chitosan–catechol will be widely used in a variety of medical settings in the future. This review focuses on the various aspects of chitosan–catechol, including its (1) preparation methods, (2) physicochemical properties, and (3) current applications.